Analisis pengaruh inflasi, suku bunga, nilai tukar, dan produk domestik bruto (PDB) terhadap harga saham pada perusahaan manufaktur subsektor textile dan garmin di bei tahun 2017-2020 - Br Manurung, Eka Yose; Nina Purnasari; Frananda Ginting (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The price of shares outstanding can measure the value of a company. There is a perfect category for the company's value if the company has a high share price. On the other hand, if the company has a low share price, the company is not in good condition. Several factors influence the increase and decrease in stock prices, such as GDP, Exchange Rates, Interest Rates, and Inflation. This study focuses on identifying whether the Garmin and Textile Sub-Sector Manufacturing Companies listed on the 2017-2020 IDX are influenced by GDP, Exchange Rates, Interest Rates, and Inflation. Researchers in this associative study uses quantitative methods. Meanwhile, Garmin and Textile Sub-Sector Manufacturing Companies are the populations in this study. From 2017-to 2020, 44 companies served as the study sample. Purposive sampling is a technique to determine the example in this study. Meanwhile, there are X4 (GDP), X3 (Exchange Rate), X2 (Interest Rate), and X1 (Inflation) as independent variables. On the other hand, Stock Price acts as Y, the dependent variable. The researcher used a significant level of 0.05 in multiple regression as a data analysis method. A company owns an unhealthy or good condition if the significance level is < 0.05.